Ruptura de pareja y estrategias de afrontamiento psicológico en adultos jóvenes. - Gaibor Mendoza, Vanessa Dayana (2024)
The main objective of this research study was to focus on the relationship breakdown which is an emotionally difficult experience that can significantly affect the mental health and well-being of young adults. This study seeks to understand how people at this stage of life experience and cope with the breakup of their romantic relationships. It aims to characterize relationship breakdown and psychological coping strategies in young adults through a literature review to examine the various aspects of relationship breakdown, including psychological, emotional, and social aspects. This project consisted of a total of 1320 scientific documents that were collected from various scientific databases such as Scielo, Proquest, Redalyc, among others. In this research a non-probabilistic purposive sampling was performed according to the selection criteria, so 72 records were chosen to be read critically and ended with 40 selected scientific articles of psychology specifically focused on the variables of study. It was determined that the breakup of a couple presents emotional consequences such as depression and distress presenting high levels of the same, when analyzing factors such as the duration of the relationship, the emotional intensity of the breakup and the presence of additional stressful events that have an impact on well-being in general. In addition, the results show the variety of coping strategies used by young adults both positive and negative in terms of positive strategies problem solving was the most used by young adults in the face of a breakup without neglecting the complexity of the coping process. At this stage of life, it is critical to create healthy and effective coping strategies that foster emotional well-being and resilience. Practical implications and suggestions aimed at supporting young adults during this emotionally challenging transition are discussed.